A CONTRASTIVE STUDY OF SOMATIC LEXEMES IN ENGLISH AND UZBEK LANGUAGES - Kholboyeva Iroda Shukhrat Kizi (Western European Studies, 2025)
This article investigates somatic lexemes in English and Uzbek, focusing on their linguistic and cultural characteristics. Somatic lexemes, derived from body parts, are deeply rooted in the cultural and cognitive frameworks of a language. This study explores their structural, semantic, and cultural features, comparing how English and Uzbek languages reflect human experience through somatic expressions
Keywords: Somatic lexemes; body parts; English